WARISAN BUDAYA DAN REFLEKSI SPIRITUAL: SASTRA ISLAM DI ERA MODERN - Khittotun Nahidin; Achmad Faroid (PPPM STIT MIFTAHUL MIDAD, 2024)
This article explores the intricate relationship between cultural heritage and spiritual reflection within the context of modern Islamic literature, emphasizing how traditional narratives continue to shape contemporary literary expressions. Drawing on qualitative data collected from semi-structured interviews and classroom observations in second semester of English Department students at STIT Miftajhul Midad Lumajang, the study reveals key themes such as the significance of classical poets like Rumi and Ibn Arabi in informing modern spiritual journeys. The participants of this study articulated how their engagement with historical texts not only enriches their literary appreciation but also fosters deeper connections to their cultural identities. Furthermore, this study highlights the role of educational environments in facilitating meaningful dialogues about cultural and spiritual themes, encouraging students to actively engage with and redefine their literary heritage. The findings underscore the importance of blending traditional and modern literary forms to address contemporary social issues, ultimately advocating for a renewed understanding of Islamic literature as a vital source of inspiration and reflection in today's rapidly changing world. This study contributes to the broader discourse on the relevance of cultural heritage in shaping spiritual and literary landscapes, paving the way for future exploration of Islamic literary traditions in modern contexts.